The interactions among gold, oil and stock market: evidence from Kuala Lumpur Composite Index (KLCI) / Siti Nur Farahim Azmi - Azmi, Siti Nur Farahim (Faculty of Business Management, 2017)
During the crisis in 2008, typical stock price decline and makes investor worried. Crisis in one country will be immediately followed by other countries in regional, because of stock price declining and crisis duration, Patel and Sarkar (1998). In this study, the focus is on the interactions between financials and commodity market. This is the biggest issues faced by investors because irregular price in one market might be effect the price index of other market. Furthermore, Korhan and Negar (2015) states that the price of gold and oil has a great impact on financial movement and all sectors of US economy. The purpose of this study is to investigate whether stock market (KLCI) has interactions between gold price volatility and oil price volatility. This research paper used regression analysis to find out the result. The data are taken from Yahoo finance data stream. In order to determine the results, the researcher use time series analysis. The data are collected from year 2011 to 2016.